Pure Endovascular Management of an Arteriovenous Malformation and an Aneurysm Both Supplied by Anterio-Inferior Cerebellar Artery: A Case Report and a Review of Literature - Khayat, Hassan A.; Alshareef, Fawaz; Alshamy, Abdulrahman; Algain, Abdulrahman; Alhejaili, Essam; Alnabihi, Omar; Alzahrani, Saeed; Stendel, Ruediger (Frontiers in Neurology, 2017)
Background and importance The tendency of posterior fossa arteriovenous malformations (pfAVM) to develop associated aneurysms (AA) is a well-known phenomenon with an increased total risk of rupture. Most pfAVM and AA develop in the territory of the posterior inferior cerebellar artery while the involvement of the anterior inferior cerebellar artery (AICA) is extremely rare. We describe an unusual case of an arteriovenous malformation (AVM) supplied by the AICA with a “proximal” AA. This unique combination of vascular lesions has been reported in only four cases so far, limiting the available experience that can safely guide the therapeutic intervention. Clinical presentation This study describes a 59-year-old female presented with a subarachnoid hemorrhage, Hunt and Hess grade 4. Angiography demonstrated an AVM fed mainly by the right AICA and draining superficially into the transverse sinus (Spetzler–Martin grade II). In addition, there was a ruptured proximal AICA aneurysm. An endovascular approach was chosen to coil the aneurysm and obliterate the AVM using ONYX in a multi-staged process. The patient recovered well without residual deficit at 6-month follow-up. Conclusion To the best of our knowledge, this is the first report describing a proximal AICA aneurysm and AVM treated by endovascular means. The outcome was very good, considering the technically demanding location. All previously reported cases with exactly similar lesions were managed surgically, with inconclusive outcomes. The data presented in this study are meant to help in decision-making process for similar cases till more data are available.